Development and validation of a nomogram for predicting the risk of cognitive impairment among chronic obstructive pulmonary diseases - Ying Fan; Chao Zhang; Zhixin Fan; Zheshu Xie; Qiuhua Sun (Annals of Medicine)
Background Cognitive impairment has been proven to have a significant impact on the overall quality of life among chronic obstructive pulmonary disease (COPD). Using a reliable and convenient method to identify the high-risk population of cognitive impairment may help to improve the prognosis of COPD patients. The aim of this study is to develop a nomogram for predicting cognitive impairment for COPD patients.Methods The convenience sampling method was employed to select COPD patients for investigation. The dataset was randomly partitioned into a development subset and a validation subset. Univariate and multiple logistic regression analyses were performed on the development dataset to ascertain risk factors for cognitive impairment and to establish a nomogram to forecast the likelihood of cognitive dysfunction in COPD patients. This model was evaluated thorough discrimination, calibration, and decision curve.Results Age, education level, regular exercise habits, participation in intellectual activities, FEV1/FVC, and serum albumin were significant contributing factors to cognitive impairment risk. A nomogram model for predicting cognitive impairment in COPD patients was developed based on these factors. The designed model demonstrates excellent predictive performance.Conclusion The designed model can identify patients at high risk of cognitive impairment, providing empirical evidence for precise treatment and management of cognitive impairment in COPD patients.